Kedudukan Wartawan Perang Dalam Konflik Bersenjata Menurut Hukum Humaniter Internasional - Dave Maynard Soselisa; Josina Augusthina Yvone Wattimena; Lucia Charlota Octovina Tahamata (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: The existence of war journalists in international humanitarian law has a very important role based on the 1949 Geneva Convention on protective measures for journalists serving on the battlefield. Journalists represent a profession that has implications for every coverage of war. However, journalists often become victims when armed conflicts occur. One of them is in the region of Burkina Faso and Afghanistan. Where, in these two countries, journalists from political groups and ISIS were killed. This research is a normative juridical research. This type of research is descriptive analytical. The problem approach used is the statutory, conceptual and case approaches. The source of legal materials used in this research is primary legal materials and secondary legal materials. Techniques and analysis of legal materials are qualitative in nature by prioritizing basic matters with what is researched and understood. The position of war journalists in armed conflicts based on HHI related to the case, includes, among other things, the position of war journalists in armed conflicts based on HHI from a human rights perspective on cases in Burkina Faso and Afghanistan; the position of war journalists in armed conflict is based on HHI from a principled perspective on cases in Burkina Faso and Afghanistan and the position of war journalists in armed conflict is based on HHI from a law enforcement perspective.